A method for controlling the microstructure and properties of ultra-high-speed laser cladding coatings
By optimizing the particle size distribution and low-temperature heat treatment of martensite stainless steel powder, the problem of traditional processes being unable to prepare convex crystal coatings is solved, and efficient coating corrosion resistance improvement and process simplification are achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202310173448.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Traditional processes cannot effectively prepare convex crystal coatings, resulting in rapid corrosion channels in ultra-high-speed laser cladding coatings in corrosive environments, reducing the corrosion resistance of the coating.
By optimizing the particle size distribution of martensite stainless steel powder, sieving with 300 mesh and 500 mesh sieve and vacuum ball milling, a double-maximum distributed powder raw material is formed, and low-temperature heat treatment is carried out under an inert atmosphere to improve powder flowability and achieve Preparation of conglomerate crystal coating.
The denseness of the coating and high interface bonding strength are achieved, which significantly improves corrosion resistance. At the same time, the process is simple and the cost is low, making it suitable for large-scale production.
Smart Images

Figure CN116791077B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials, and in particular to a method for realizing the control of the microstructure and properties of an ultra-high-speed laser cladding coating. Background Art
[0002] As a new type of surface coating preparation technology, ultra-high-speed laser cladding technology is often used to improve the corrosion resistance and wear resistance of material surfaces. Therefore, it is widely used in industries and fields such as aerospace, petrochemicals, mining and metallurgy, transportation and precision manufacturing.
[0003] The service performance of materials is closely related to their inherent microstructure, so the microstructure regulation of ultra-high-speed laser cladding coatings has become one of the key development directions urgently needed in this field of technology. Similar to traditional laser cladding, ultra-high-speed laser cladding coatings are mainly composed of three parts: 1) equiaxed crystal zone on the surface; 2) columnar crystal zone in the middle; 3) plane crystal at the bottom. However, due to the larger temperature gradient of ultra-high-speed laser cladding, its grains are finer and its columnar crystal zone is more significant. Due to the preferential growth of grains in the opposite direction of the temperature gradient, ultra-high-speed laser cladding coatings usually show obvious preferential orientation, which leads to obvious differences in the mechanical properties of the coating along the tangential and normal directions of the substrate surface. In addition, there are a large number of eutectic structures between columnar dendrites in ultra-high-speed laser cladding coatings; eutectic carbides will cause chromium depletion near the interface. In a corrosive environment, the corrosive liquid is very likely to corrode rapidly along the two-phase interface. Since these interfaces are approximately perpendicular to the substrate surface, these interfaces become rapid corrosion channels, which eventually lead to corrosion failure of the coating.
[0004] But compared with columnar crystals, equiaxed crystal interfaces are more "tortuous" and have better corrosion resistance. However, the traditional process parameter control method cannot prepare a fully equiaxed crystal structure coating. In order to further improve the coating structure performance, a new coating structure control method with low cost and simple process is urgently needed at this stage to realize the preparation of fully equiaxed crystal coatings. Summary of the invention
[0005] The purpose of the present invention is to provide a method for controlling the microstructure and properties of an ultra-high-speed laser cladding coating, which further improves the microstructure and properties of the coating and realizes the preparation of a fully equiaxed crystal coating; and the method has low cost and simple process.
[0006] In order to achieve the above technical objectives, the present invention provides a method for controlling the microstructure and properties of ultra-high-speed laser cladding coatings, which is based on the optimization of the particle size of martensitic stainless steel powder and controls the particle size distribution of the powder raw materials to achieve rapid preparation of fully equiaxed crystal coatings; the powder material particle size distribution control method comprises the following steps:
[0007] (1) The martensitic stainless steel powder prepared by vacuum gas atomization was sieved with 300 mesh and 500 mesh sieves to obtain powders with a particle size distribution of 30-50 μm, which are represented by A;
[0008] (2) The remaining martensitic stainless steel prepared by vacuum gas atomization is sieved with 500 mesh and 800 mesh sieves to obtain powders with a particle size distribution of 15-30 μm, which are denoted by B;
[0009] (3) mixing powders A and B in a ratio of 1:3 to 1:2, and then ball milling to obtain a metal powder raw material with a bimodal particle size distribution;
[0010] (4) The metal powder raw material is placed in a tube furnace and subjected to low-temperature heat treatment under an inert atmosphere to improve the powder fluidity, thereby obtaining powder M-1.
[0011] In step (3), in order to prevent oxidation of the powder, the powder is mixed by a vacuum ball mill with a rotation speed of 100-200 rpm, a ball milling time of 6-8 hours, and a ball-to-material ratio of 1:1.
[0012] Wherein, in step (4), the low temperature heat treatment temperature is 100-150°C and the heat preservation time is 3-4h.
[0013] Among them, the D50 of powder M-1 is 30~35µm and the fluidity is 25~30s / 50g.
[0014] Wherein, the martensitic stainless steel powder comprises the following components by mass percentage: C: ≤0.2%, Cr: 15.0~17.0%, Ni: 1.25~2.50%, Mn: ≤1.0%, Si: ≤1.0%, and Fe balance.
[0015] The rapid preparation method of the fully equiaxed crystal coating comprises the following steps:
[0016] (1) First, the workpiece surface is machined to remove surface rust or stains; then the surface is cleaned with alcohol to remove residual oil or metal debris on the surface;
[0017] (2) Install the workpiece, position the workpiece, and load powder M-1 into the powder feeder;
[0018] (3) Set the laser power, travel speed, powder feeding rate, and spot diameter, and start the ultra-high-speed laser cladding equipment;
[0019] (4) After the cladding process is completed, the coating is naturally cooled to room temperature; then the coating surface is machined to obtain a specimen with qualified size, accuracy and surface quality.
[0020] Wherein, in step (3), the laser power is 1200-2200 W, the spot diameter is 1.00 mm, the travel speed is 15-45 m / s, and the powder feeding amount is 25-35 g / min. Beneficial Effects
[0021] The present invention provides a method for realizing the control of the microstructure and properties of an ultra-high-speed laser cladding coating, which has the following beneficial effects:
[0022] 1. This application uses the concept of semi-solid solidification, adjusts the powder particle size distribution, and combines the characteristics of ultra-high-speed laser melting and cladding (small molten pool, short solidification time, etc.) to partially melt the powder in the molten pool, thereby maintaining a certain amount of unmelted grains inside the molten pool. These unmelted grains serve as heterogeneous cores for crystal nucleation, realizing the transformation of grains from columnar dendrites to equiaxed dendrites. Compared with the case where all the powder is melted, this artificially controlled semi-solid solidification process has significantly different physical and chemical processes and solute diffusion effects, and the phase composition and distribution of the material deposition coating, the type and distribution of the second phase, the substructure and other microstructure characteristics and mechanical properties are also significantly different.
[0023] 2. The coating prepared by the method of the present invention is dense, free of defects such as pores and cracks, and is metallurgically bonded to the substrate with high interface bonding strength.
[0024] 3. The method of the present invention can be used to prepare a fully equiaxed crystal coating, which can significantly improve the corrosion resistance of the coating.
[0025] 4. The process of the present invention is simple, low in cost, highly controllable and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The scanning electron microscope morphology of the two powders M-1 and M-2 in the embodiment;
[0027] Figure 2 This is a scanning electron microscope (low magnification) observation image of the ultra-high-speed laser cladding coating of powder M-1 and powder M-2 in the embodiment;
[0028] Figure 3 This is a high-magnification scanning electron microscope (high-magnification) observation image of the middle position of the ultra-high-gloss cladding coating of the powder M-1 and the powder M-2 of the embodiment;
[0029] Figure 4 The XRD results of the two coatings of Example powder M-1 and M-2 are shown;
[0030] Figure 5 The hardness test results of two coatings in the embodiment are shown in FIG.
[0031] Figure 6The results of the salt spray test (1000 h) of the coatings of Examples M-1 and M-2 are shown. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0033] In this example, ultra-high-speed laser cladding was used to repair the surface of a piston rod of a petroleum company.
[0034] This embodiment provides a method for controlling the microstructure and properties of ultra-high-speed laser cladding coatings. It is based on the optimization of the particle size of martensitic stainless steel powder and controls the particle size distribution of the powder raw materials to achieve rapid preparation of fully equiaxed crystal coatings. Among them, the piston rod substrate is 45# steel, and its chemical composition is calculated by mass percentage: C: 0.42~0.50%; Cr: ≤0.25%; Mn: 0.50~0.80T; Ni: ≤0.25T; P: ≤0.035%; S: ≤0.035T; Si: 0.17~0.37T, and the rest is Fe. The martensitic stainless steel powder contains the following components by mass percentage: C: 0.11%, Cr: 16%, Ni: 1.64%, Mn: 0.74%, Si: 0.75%, and Fe balance.
[0035] First, the powder material particle size distribution control method includes the following steps:
[0036] S1. First, the martensitic stainless steel powder prepared by vacuum gas atomization is sieved with 300 mesh and 500 mesh sieves to obtain powders with a particle size distribution of 30-50 μm, which are represented by A.
[0037] S2, then sieving the remaining martensitic stainless steel prepared by vacuum gas atomization with 500 mesh and 800 mesh sieves to obtain powders with a particle size distribution of 15-30 μm, which are represented by B;
[0038] S3, mixing powders A and B in a ratio of 1:3, and then vacuum ball milling for mixing the powders, with a rotation speed of 150 rpm, a ball milling time of 7 hours, and a ball-to-material ratio of 1:1, and finally obtaining two metal powder raw materials with significantly different particle size distributions;
[0039] S4. Place the metal powder raw material powder in a tube furnace and perform low temperature heat treatment under an inert atmosphere at a temperature of 120°C for 3.5 hours to improve the powder fluidity, thereby obtaining powder M-1. The D50 of powder M-1 is 30~35µm, and the fluidity is 25~30s / 50g.
[0040] Then the repair process is carried out, and the ultra-high laser cladding surface preparation method for piston rod repair is as follows:
[0041] (1) First, the workpiece surface is machined to remove surface rust or stains; then the surface is cleaned with alcohol to remove residual oil or metal debris on the surface;
[0042] (2) Install the workpiece, position the workpiece, and load powder M-1 into the powder feeder;
[0043] (3) Set the laser power, travel speed, powder feeding rate, and spot diameter. After all parameters are set, start the ultra-high-speed laser cladding equipment; the laser power is 1600W, the spot diameter is 1mm, the feed speed is 1mm / r, the linear speed is 25m / s, and the powder feeding rate is 30g / min;
[0044] (4) After the cladding process is completed, the coating is naturally cooled to room temperature; then the coating surface is machined to obtain a specimen with qualified size, accuracy and surface quality, and finally cleaned with anhydrous ethanol and dried naturally. Example
[0045] In this example, the surface of the petroleum plunger is repaired by ultra-high-speed laser cladding in order to improve the corrosion and wear resistance of the surface.
[0046] This embodiment provides a method for achieving the control of the microstructure and properties of ultra-high-speed laser cladding coatings. It is based on the optimization of the particle size of martensitic stainless steel powders. By controlling the particle size distribution of the powder raw materials, the rapid preparation of fully equiaxed crystal coatings is achieved. Among them, the composition and mass fraction of the petroleum plunger material are: C: 0.32-0.40; Si: 0.17-0.37; Mn: 0.40-0.70; Cr: 0.80-1.10; Ni: ≤0.030; Cu: ≤0.030; Mo: 0.15-0.25, and the rest is Fe. The martensitic stainless steel powder contains the following components by mass percentage: C: 0.15%, Cr: 15%, Ni: 2.5%, Mn: 1.0%, Si: 1.0%, and Fe balance.
[0047] First, the powder material particle size distribution control method includes the following steps:
[0048] S1. First, the martensitic stainless steel powder prepared by vacuum gas atomization is sieved with 300 mesh and 500 mesh sieves to obtain powders with a particle size distribution of 30-50 μm, which are represented by A.
[0049] S2, then sieving the remaining martensitic stainless steel prepared by vacuum gas atomization with 500 mesh and 800 mesh sieves to obtain powders with a particle size distribution of 15-30 μm, which are represented by B;
[0050] S3, mixing powders A and B in a ratio of 1:2, and then vacuum ball milling for mixing the powders, with a rotation speed of 100 rpm, a ball milling time of 8 hours, and a ball-to-material ratio of 1:1, and finally obtaining two metal powder raw materials with significantly different particle size distributions;
[0051] S4. Place the metal powder raw material powder in a tube furnace and perform low-temperature heat treatment in an inert atmosphere at a temperature of 100°C for 4 hours to improve the powder fluidity, thereby obtaining powder M-1; the D50 of powder M-1 is 30~35µm, and the fluidity is 25~30s / 50g.
[0052] Then the repair process is carried out, and the ultra-high laser cladding surface preparation method for piston rod repair is as follows:
[0053] (1) First, the workpiece surface is machined to remove surface rust or stains; then the surface is cleaned with alcohol to remove residual oil or metal debris on the surface;
[0054] (2) Install the workpiece, position the workpiece, and load powder M-1 into the powder feeder;
[0055] (3) Set the laser power, travel speed, powder feeding rate, and spot diameter. After all parameters are set, start the ultra-high-speed laser cladding equipment; the laser power is 2000W, the spot diameter is 1mm, the feed speed is 0.5mm / r, the linear speed is 15m / s, and the powder feeding rate is 30g / min;
[0056] (4) After the cladding process is completed, the coating is naturally cooled to room temperature; then the coating surface is machined to obtain a specimen with qualified size, accuracy and surface quality, and finally cleaned with anhydrous ethanol and dried naturally. Example
[0057] In this example, ultra-high-speed laser cladding is performed on the inside of the oil pipe to improve the corrosion and wear resistance of the inner surface of the oil pipe.
[0058] This embodiment provides a method for achieving the control of the microstructure and properties of ultra-high-speed laser cladding coatings. It is based on the optimization of the particle size of martensitic stainless steel powders, and by controlling the particle size distribution of the powder raw materials, the rapid preparation of fully equiaxed crystal coatings is achieved. Among them, the chemical composition of the oil pipe material and its mass percentage are: C: 0.37-0.45; Si: 0.4-0.7; Mn: 1.3-1.8; S: ≤0.04; P: ≤0.04, and the rest is Fe. The martensitic stainless steel powder contains the following components by mass percentage: C: 0.2wt.%, Cr: 17%, Ni: 1.250wt.%, Mn: 0.8%, Si: 0.7%, and Fe balance.
[0059] First, the powder material particle size distribution control method includes the following steps:
[0060] S1. First, the martensitic stainless steel powder prepared by vacuum gas atomization is sieved with 300 mesh and 500 mesh sieves to obtain powders with a particle size distribution of 30-50 μm, which are represented by A.
[0061] S2, then sieving the remaining martensitic stainless steel prepared by vacuum gas atomization with 500 mesh and 800 mesh sieves to obtain powders with a particle size distribution of 15-30 μm, which are represented by B;
[0062] S3, mixing powders A and B in a ratio of 1:3, and then vacuum ball milling for mixing the powders, with a rotation speed of 200 rpm, a ball milling time of 6 hours, and a ball-to-material ratio of 1:1, and finally obtaining two metal powder raw materials with significantly different particle size distributions;
[0063] S4. Place the metal powder raw material powder in a tube furnace and perform low temperature heat treatment under an inert atmosphere at a temperature of 150°C for 3 hours to improve the powder fluidity, thereby obtaining powder M-1. The D50 of powder M-1 is 30~35µm, and the fluidity is 25~30s / 50g.
[0064] Then the repair process is carried out, and the ultra-high laser cladding surface preparation method for piston rod repair is as follows:
[0065] (1) First, the workpiece surface is machined to remove surface rust or stains; then the surface is cleaned with alcohol to remove residual oil or metal debris on the surface;
[0066] (2) Install the workpiece, position the workpiece, and load powder M-1 into the powder feeder;
[0067] (3) Set the laser power, travel speed, powder feeding rate, and spot diameter. After all parameters are set, start the ultra-high-speed laser cladding equipment; the laser power is 1200W, the feed speed is 1.5mm / r, the line speed is 40m / s, the spot diameter is 1mm, and the powder feeding amount is 30g / min;
[0068] (4) After cladding is completed, the coating is cooled naturally to room temperature. Finally, it is processed into the target size and the coating quality is tested.
[0069] Comparative Example
[0070] Compared with Example 1, the powder M-2 used in the comparative example is obtained by mixing powder A and powder B in a ratio of 3:1, and other parameter conditions and preparation process are consistent with Example 1.
[0071] Related tests:
[0072] The particle size, fluidity and morphology of the M-1 powder in Example 1 and the M-2 powder in Comparative Example 1 were tested. The results of the particle size and powder fluidity tests are shown in the following table.
[0073] Figure 1 The scanning electron microscope morphology of M-1 and M-2 powders, (a) M-1 powder and (b) M-2 powder, from Figure 1 It can be seen that the M-1 powder has a higher fine powder content and its particle size is significantly smaller than that of the M-2 powder.
[0074] Figure 2 This is a scanning electron microscope observation of the ultra-high-speed laser cladding coatings of powder M-1 and powder M-2. Figure 2 (a) shows M-1 powder, (b) shows M-2 powder. Figure 2 It can be clearly seen that the M-1 coating is equiaxed crystals from the fusion line to the coating surface, while the M-2 coating is similar to ordinary laser cladding, and is divided into three parts from the fusion line to the coating surface: 1) bottom plane crystals; 2) middle columnar crystals; 3) surface equiaxed crystals.
[0075] Figure 3 This is a high-magnification scanning electron microscope observation of the middle position of the ultra-high gloss cladding coating of powder M-1 and powder M-2. Figure 3 (a) shows M-1 powder, and (b) shows M-2 powder. The microstructures of M-1 coating and M-2 coating are obviously different. The M-1 coating has a coarser structure and is in the form of equiaxed dendrites, with a large amount of eutectic structures distributed between the dendrites; while the M-2 coating has a finer structure and is in the form of columnar dendrites, with a large amount of eutectic structures distributed between the dendrites.
[0076] Figure 4 These are the XRD results of the M-1 and M-2 coatings. Figure 4(a) shows M-1 powder, (b) shows M-2 powder. Figure 4 It can be seen that both M-1 and M-2 coatings are mainly composed of BBC martensite and FCC retained austenite. However, compared with M-2 coating, the content of retained austenite in M-1 coating is higher.
[0077] Figure 5 These are the hardness test results of two coatings. In each set of test results, the left side is the M-1 coating, and the right side is the M-2 coating; Figure 5 It shows that the hardness of the M-1 coating is slightly lower than that of the M-2 coating, which may be related to the coarse structure and higher content of retained austenite in the M-1 coating.
[0078] Figure 6 The results of the salt spray test (1000h) of M-1 and M-2 coatings are shown below. Figure 4 (a) shows M-1 powder and (b) shows M-2 powder, which shows that under the same process and composition conditions, the M-1 coating has better corrosion resistance.
[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for controlling the microstructure and properties of ultra-high-speed laser cladding coatings, characterized in that: Based on the optimization of the particle size of martensitic stainless steel powder, the rapid preparation of the fully equiaxed crystal coating is achieved by controlling the particle size distribution of the powder raw material; the method for controlling the particle size distribution of the powder material includes the following steps: (1) The martensitic stainless steel powder prepared by vacuum gas atomization was sieved with 300 mesh and 500 mesh sieves to obtain powders with a particle size distribution of 30-50 μm, which are represented by A; (2) The remaining martensitic stainless steel prepared by vacuum gas atomization is sieved with 500 mesh and 800 mesh sieves to obtain powders with a particle size distribution of 15-30 μm, which are denoted by B; (3) mixing powders A and B in a ratio of 1:3 to 1:2, and then ball milling to obtain a metal powder raw material with a bimodal particle size distribution; (4) placing the metal powder raw material in a tube furnace and performing low-temperature heat treatment under an inert atmosphere to improve the powder fluidity, thereby obtaining powder M-1; The martensitic stainless steel powder comprises the following components by mass percentage: C: ≤0.2%, Cr: 15.0-17.0%, Ni: 1.25-2.50%, Mn: ≤1.0%, Si: ≤1.0%, and Fe balance; The D50 of powder M-1 is 30~35µm and the flowability is 25~30s / 50g; The rapid preparation of the fully equiaxed crystal coating comprises the following steps: (1) First, the workpiece surface is machined to remove surface rust or stains; then the surface is cleaned with alcohol to remove residual oil or metal debris on the surface; (2) Install the workpiece, position the workpiece, and load powder M-1 into the powder feeder; (3) Set the laser power, travel speed, powder feeding rate, and spot diameter, and start the ultra-high-speed laser cladding equipment; among them, the laser power is 1200-2200W, the spot diameter is 1.00mm, the travel speed is 15-45m / s, and the powder feeding rate is 25-35g / min (4) After the cladding process is completed, the coating is naturally cooled to room temperature; then the coating surface is machined to obtain a specimen with qualified size, accuracy and surface quality.
2. A method for controlling the microstructure and properties of ultra-high-speed laser cladding coatings according to claim 1, characterized in that: In step (3), in order to prevent the powder from being oxidized, the powder is mixed by vacuum ball milling, with a rotation speed of 100-200 rpm, a ball milling time of 6-8 h, and a ball-to-material ratio of 1:
1.
3. The method for realizing the control of the microstructure and properties of ultra-high-speed laser cladding coating according to claim 1 is characterized in that: In step (4), the low temperature heat treatment temperature is 100-150°C and the heat preservation time is 3-4h.
